Pengaruh Social Media Marketing, Brand Awareness, Dan Brand Image Terhadap Brand Loyalty Pada J&T Express Di Surabaya - Sri Yunan Budiarsi; Monica Adjeng Erwita; Jessica Netanya Siregar (Majalah Ekonomi, 2021)
Currently, the internet has a very big influence on the market which must be supported by delivery services so that it can reach consumers. Through the use of internet technology, using social media as a promotional event will create brand awareness and a good brand image, which in turn are expected to foster company loyalty. This study aims to analyze the effect of social media marketing, brand awareness, and brand image on brand loyalty at J&T Express in Surabaya. The sampling technique used was non probability sampling by means of purposive sampling. The sample used in this study was 150 respondents. The characteristics of respondents in this study were respondents who had made transactions at J&T Express in Surabaya. Data were collected using a questionnaire. The data analysis technique used is SEM analysis with the LISREL program. The research results prove that Social Media Marketing has a significant influence on Brand Awareness; Social Media Marketing has a significant influence on Brand Image; Brand Awareness has a significant influence on Brand Loyalty; Brand Image has a significant influence on Brand Loyalty; Social Media Marketing has a significant influence on Brand Loyalty. This research is expected make more use of social media marketing as a tools of communication which later will affect awareness, brand image, and loyalty.